(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available. Key words: Glycine max; cotyledon; fatty acid; lipid; RT-PCR Bangladesh j. genet. biotechnol. 6 (1&2): 45-49, 2005 (June & December)